Estimation of the Duration of Post-partum Amenorrhea among Nepalese Mothers: Some Indirect Techniques - Aryal, Tika Ram (Nepal Journal of Science and Technology, 2010)
The main aim of this paper is to use some indirect techniques to estimate the duration of post-partum amenorrhea (PPA) among Nepalese mothers by using the data of Ministry of Health (MOH 2001,2006). The techniques used are based on two types of data, i.e., duration of PPA and breastfeeding (BF). Among the techniques, the one developed by Aryal (2008) provided a very close estimate of the duration of PPA period among Nepalese mothers. The estimated average PPA period was found to be 11.8 months against the observed value of 11.1 months in 2001 data (MOH 2001) while it was 10.3 months against the observed value of 9.3 months in 2006 data (MOH 2006). Estimated PPA period was found to be much close especially by fitting the inverse and logarithmic models. In addition to this, duration of PPA period was also estimated in relation to the characteristics of mothers and the results were found to be consistent with the observed values. It is therefore the used techniques provided very close estimate of PPA period, which might be an applicable technique to estimate the duration of PPA period for any population if the data of the duration of breastfeeding are available. Key words: Post-partum amenorrhea; Breastfeeding; Indirect-technique; Curves fitting; Fertility DOI: 10.3126/njst.v10i0.2963 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 213-218